CO tolerant Pt/Ru0.7Ti0.3O2 nanocatalyst for hydrogen oxidation reaction - Maja D. Obradović; Snežana Lj. Gojković (Zaštita Materijala)
The oxidation of pure H2 and H2/CO mixture (100 ppm CO) was investigated on Pt nanocatalyst supported on Ru0.7Ti0.3O2 (Pt /Ru0.7Ti0.3O2) by linear sweep voltammetry at a rotating disc electrode in 0.1 M HClO4. The results were compared with those on the commercial Pt/C catalyst. It was demonstrated that Pt/Ru0.7Ti0.3O2 electrode possesses good conductivity and stability of the supports in the electrochemical experiments. The onset potential of COads oxidation on Pt/Ru0.7Ti0.3O2 is lower than Pt/C indicating that the Pt nanoparticles are in close contact with Ru atoms from support, which enable bifunctional mechanism and electronic effects to be operable. The influence of the poisoning of Pt/Ru0.7Ti0.3O2 and Pt/C catalyst by COads on the HOR was examined at several surface coverages ranging from 0 to 0.6. The decrease in HOR current on COads poisoned surface in low over-potential region of 0.05-0.50 V is less pronounced on Pt/Ru0.7Ti0.3O2 than on Pt/C. This is ascribed to a weakening of the Pt-CO interaction and consequently higher mobility of COads on Pt particles contacting Ru from the Ru0.7Ti0.3O2 support.